PERANAN GENDER DALAM PENANGGULANGAN KEMISKINAN - hamsidar, hj (PSW, 2010)
In repertoire of postcolonial theory, found translational process that include local and eastern thinking into the development paradigm of domination. Unfortunately, in this translation process constructed a new hegemony of the eastern womenâs weaknesses in term of both men and women of east west. In such a constellation, mainstream gender could became a new problem when theÂ from of new thinking to realize that intervene and suppress various local gender narratives in Indonesia. Deconstruction efforts should be accompanied with the construction of a new discourse of justification reversal (this time can also read :hegemonic) from of existence of the problem of development projects, the existence the ownership of women (rather than explore the issue in women).